Occupational exposure monitoring for radon in various manufacturing workplaces and underground public-use facilities in Korea. Issue 3 (23rd January 2023) - Lee, Seokwon; Lim, Daesung; Seo, Sungchul
Abstract : We characterized radon exposure levels at the workplaces and underground public-use facilities using short/long-term, and real-time detectors. The mean radon level in the underground facilities was observed 1.8-fold higher than that at workplaces. Abstract : In this study, we measured the levels of occupational radon using short-term (electret passive environmental radon monitor system [E-PERM®]), long-term (Radtrak2® alpha track), and real-time (RAD7) monitoring detectors and characterized radon exposure levels in workplaces directly handling radon raw materials and byproducts and underground public-use facilities likely to be exposed to radon in the form of a naturally occurring radioactive material (NORM). The geometric means (GMs) of occupational radon exposures measured at 10 manufacturing workplaces and 11 underground public-use facilities were 86.4 Bq m −3 ( n = 299) overall, 60.7 Bq m −3 ( n = 91) for short-term measurements, 132.4 Bq m −3 ( n = 176) for long-term measurements, and 30.0 Bq m −3 ( n = 32) for real-time measurements. More importantly, the GM of radon levels measured at the underground facilities [118.9 Bq m −3 ( n = 127)] was significantly higher than that found at the workplaces [68.3 Bq m −3 ( n = 172)] ( p < 0.001). We found that workers at underground public-use facilities could be unintentionally exposed to higher radon levels resulting from NORMs. Therefore, we suggest that the Korean Occupational Safety and Health Act strengthens the regulations related to occupational exposure management for radiation and radon and establishes a more comprehensive control system to regularly monitor, manage, and reduce the levels of occupational radon exposure, particularly NORMs. In doing so, we can protect workers' health and safety from potential radon exposure at various workplaces and underground public-use facilities. Further studies should be conducted to quantitatively evaluate occupational radon exposures for a larger number of other underground facilities and workplaces, build radon-specific job or task-based exposure matrices, and follow-up health effects for workers who could possibly be exposed to radon or NORMs.